Long-term trends of microplastics in seawater and farmed oysters in the Maowei Sea, China. (15th March 2021) - Zhu, Jingmin; Zhang, Qiang; Huang, Yinan; Jiang, Yuping; Li, Jiana; Michal, Jennifer J.; Jiang, Zhihua; Xu, Youhou; Lan, Wenlu
Abstract: Microplastic pollution in marine environments and organisms has received a great deal of international attention. However, the long-term field studies of microplastics are rare. Here, we assessed annual variation in microplastic abundance in the Maowei Sea, a classic mariculture bay in southern China, and analyzed the long-term accumulation in oyster tissues. U-shaped time trends of microplastics in water were observed from January to December in 2018 in the estuarine region, inner bay, and mouth bay sites, representing an inverse relationship with the local rainfall patterns. The common microplastic particles in Maowei Sea are PET/PE fibers, and polystyrene foams, which are mainly related to textile pollution and fishery activities. After one year of continuous monitoring, we did not find accumulation of microplastics in the whole soft tissues of oyster after 10% KOH digestion. No significant correlation of microplastic abundances between water and oysters was observed. The microplastic abundance in oyster was correlated with some environmental variables (i.e. salinity, pH, nutrients and total organic carbon) of the surrounding water following Spearman correlation analysis. The microplastic levels in oysters could probably be influenced by the environmental variables. Graphical abstract: Image 1 Highlights: The microplastic pollution in Maowei Sea is likely related to textile pollution and fishery activities. The time trends of microplastic abundances in Maowei Sea had an inverse relationship with rainfall. No bioaccumulation of microplastics in oyster was observed after one year of monitoring. No significant correlation of microplastic abundances between water and oysters was observed. Abstract : U-shaped time trends of microplastics in water were observed in 2018 in the Maowei Sea, and no bioaccumulation of microplastics in oysters after one year of monitoring.